2016
DOI: 10.1016/j.jalz.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of subjective cognitive decline criteria in research studies

Abstract: INTRODUCTION Subjective Cognitive Decline (SCD) manifesting prior to clinical impairment could serve as a target population for early intervention trials in Alzheimer’s disease (AD). A working group, the Subjective Cognitive Decline Initiative (SCD-I), published SCD research criteria in the context of preclinical AD. To successfully apply them, a number of issues regarding assessment and implementation of SCD needed to be addressed. METHODS Members of the SCD-I met to identify and agree upon topics relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
447
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 424 publications
(491 citation statements)
references
References 108 publications
9
447
0
6
Order By: Relevance
“…One recent report indicated that 34 self-report measures are being used across 19 international studies of SCD [26]. At present, there is no “gold standard” method of SCD assessment [44]. However, the single item used in our study did not allow us to assess SCD severity and it may have restricted our ability to capture complaints in domains other than memory, which can be affected early in non-amnestic types of dementia.…”
Section: Discussionmentioning
confidence: 96%
“…One recent report indicated that 34 self-report measures are being used across 19 international studies of SCD [26]. At present, there is no “gold standard” method of SCD assessment [44]. However, the single item used in our study did not allow us to assess SCD severity and it may have restricted our ability to capture complaints in domains other than memory, which can be affected early in non-amnestic types of dementia.…”
Section: Discussionmentioning
confidence: 96%
“…Future studies would be strengthened by using well-validated SCD instruments specifically designed for Hispanic older adults. It is worth noting however, that there is still no gold standard measure to assess SCD [10], especially for Hispanics living in the United Stated (where research is lacking). As such, we view the current findings as a first attempt to replicate previous findings in non-Hispanic Whites, with hopes of improving the measurement of SCD in Hispanics and non-Hispanic Whites as new validated instruments become available in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors such as personality traits and cultural background might also be related to SCD, but little research has been done outside of non-Hispanic White older adult cohorts [57]. The Subjective Cognitive Decline Initiative (SCD-I) Working Group recently published recommendations for the implementation of SCD criteria in research studies and mentioned that “further work is needed to determine whether SCD may manifest differently in different racial or ethnic groups” [10]. As such, it is important for the SCD research field to examine if the relationship between SCD scores, cognitive performance, and symptoms of depression in Hispanics is similar to that previously observed in non-Hispanic Whites.…”
Section: Introductionmentioning
confidence: 99%
“…SCD was assessed using the Memory failures in everyday life following severe head injury [28] and the Subjective Cognitive Decline Questionnaire (SCD-Q) [29]. Although SCD has been recently included in the preclinical stage of AD [30, 31], its identification in the healthy aging population is essential [32] due to their association with a higher risk of AD [33, 34]. …”
Section: Methodsmentioning
confidence: 99%